Taxes Today, Benefits Tomorrow - Thomas Le Barbanchon (Institute of Labor Economics (IZA), 2025)
This paper tests whether partially unemployed workers value future preserved benefits when they bunch at the kink of the unemployment insurance benefit-withdrawal schedule. I extend the bunching formula of Saez (2010) to a dynamic setting that accounts for the value of future benefits tied to taxation. This yields new tests of tax-benefit linkage based on bunching heterogeneity. I verify in quasi-experiments that UI extension programs that decrease the value of future benefits lead to more bunching and to lower labor supply. Last, a quantification exercise of the dynamic bunching formula provides extra support for a strong tax-benefit linkage.
Keywords: J65; H24; H31; 330; tax-benefit linkage; bunching; unemployment insurance